Cuidemos nuestros sentidos - Rios Villegas, Patricia Elena (2018)
The present work of professional sufficiency entitled "Let's take care of our senses", part of the systematic observation of the problems found in the teaching-learning process of primary-level students in the area of science and technology in the educational institution where I work, It has as a fundamental purpose to design, implement, execute and evaluate a learning session with its respective theoretical-scientific and technical-pedagogical support. For the elaboration of this work, the methodology of qualitative research was used at a basic theoretical level proposition, resorting to the use of the learning scheme given by the PREFORD program of the National University of Trujillo and all the bibliographic material found in various sources from both physical libraries as well as virtual ones. As a general conclusion we have, on the one hand, that pedagogy is the theoretical science that studies education as a process of integral formation of man, they use the other social sciences, such as anthropology, psychology, economics, among others., to have a deep understanding of the student as a being in the process of training and development, in addition, it guides didactics as an applied science that studies the teaching-learning process, and on the other hand, that the human body has a series of concentrated receptors in the sense organs, the same that allow us to connect with the outside world, capture its qualities, components, functions and relationships (sensations, perceptions and representations), transmit them through neurotransmitters to the central nervous system and produce abstractions in the form of concepts, judgments and reasoning; consequently they must be protected and developed.